Indikasi Dampak Sosial Ekonomi dan Lingkungan Proyek Infrastruktur Bendung Irigasi Pertanian di Kelurahan Baliase, Kemacatan Masamba, Kabupaten Luwu Utara - Radinal Jayadi; Muhammad Fathien Azmy; Yashinta Kumala Dewi Sutopo (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2015)
The construction of agricultural irrigation weir infrastructure in Baliase Village aims to irrigate 20,000 Ha of agricultural land in six sub-districts in North Luwu Regency as a solution to the lack of water resources for agricultural lands. The purpose of this study is to describe the condition of the food crop sub sector Kab. North Luwu on the development of the agricultural sector in the province of South Sulawesi, assessing indications of the impact of dam construction on social, economic and environmental aspects and devising strategies to mitigate the impact in maximizing the potential existence of dam infrastructure. The results of the study of the condition of the food crop sub sector are relatively small seen from agricultural productivity, LQ value <1 and RC value <1. Indications of the impact of the construction of weir infrastructure namely, opening of employment by 120,000 people / ha with employment opportunities 35.40% employment participation rate 0.27%, opening of business opportunities in rice factories, rice plows and trade in agricultural products, increasing productivity of 7 tons / ha of crops rice and horticultural crops 2.8 Tons / Ha, increasing the income of lowland rice farmers to Rp. 1,042,920,000,000 and horticultural crop farmers Rp. 56,508,750,000, supply of clean water needs 25,900,000 Liters / Day, increase (GRDP) to Rp 1,878,848,086,000, intensification of agricultural land to 14,948 Ha, increase in sand and gravel gap, change in sidiment transport to 0.02872 Mg / sec and endangered eel and giant prawns.